Jagat Saksana Ladi: Servant Leadership in the Perspective of Javanese Culture in Surakarta - Aditya, Ivan; Aji, Aditia Permana; Halyandi, Anang Akbar Rizky Putra; Haq, Muhammad Robeeth Fauzal; Putri, Noor Rizky Tiara; Mulyadi, Asal Wahyuni Erlin (Journal of Leadership in Organizations, 2026)
Introduction/Main Objectives: This research explores the application of Servant Leadership through a Javanese cultural lens among public sector leaders in Surakarta. Background Problems: The evolving leadership paradigm requires an understanding of how local implementation is and of the concept of Servant Leadership within the hierarchical Javanese context. Novelty: A theoretical gap exists in integrating Western service models with unique Javanese cultural values. "Jagat Saksana Ladi" framework showing how Javanese cultural leadership values modify and reinforce the universal characteristics of Servant Leadership. Research Methods: We conducted a phenomenological study using in-depth interviews with public organization leaders across various clusters to explore their lived experiences. Finding/Results: Leaders merge broad vision (Jagat), exemplary conduct (Saksana), and service-driven action (Ladi). This empirical alignment confirms that culturally contextualized Servant Leadership is internalized as a spiritual and ethical philosophy. Conclusion: Servant leadership in Surakarta reflects a deep internalization of Javanese ethics, demonstrating that culturally adaptive leadership is vital for inclusive public service, highlighting the need for broader cross-cultural research.